Research potential of wood of barrels from Roman water wells - Čufar, Katarina (Les (Ljubljana), 2019)
During archaeological excavations on wet sites in the area of the ancient Roman Nauportus (today's Vrhnika, Slovenia) in 2005, preserved parts of various wooden structures were discovered. We collected and investigated almost 500 samples of wood from these. Half of the samples were silver fir (Abies alba) and oak ( Quercus sp.). In particular, we focused on the dendrochronological investigation of three barrels made of silver fir wood, which were used to con- solidate the walls of the three water wells. First, we constructed and dated a silver fir tree-ring chronology with the help of teleconnection. Afterward, we dated the barrels with the end dates: barrel 1 % end date 10 AD, barrel 2 % end date 3 AD, and barrel 3 % end date 10 AD. All dates represent the terminus post quem , after which the barrels were made and used for wells. The time frame for the construction of wells was complemented by the dates we obtained by analysing archaeological finds on the same site. The barrels from Nauportus were compared with contemporaneous barrels from water wells recently excavated in Emona (today's Ljubljana, Slovenia). The barrels are among the first successfully dendrochronologically dated wooden remains from the 1st Century AD in Slovenia. They will allow for the better dating of stratigraphic archaeological layers, construction phases and individual archaeological finds in the wider area south of the Alps in the period soon after it was occupied by the Romans.
Keywords: Abies alba; archaeology; arheologija; dendrochronology; dendrokronologija; leseni sodi; moisture content; rimska doba; vodnjaki; wells; wooden barrels